Electromagnetic properties of polyester moulding reinforced waste metal lathes - Iswandi Idris (International Conference on Industrial Revolution for Polytechnic Education, 2019)
Research on polymer reinforced composites using raw materials from nature and waste utilization has begun to be developed, Scope and Objectives of this study include: To improve the electromagnetism characteristics of waste metal reinforced polyester composite lathes through gravity, DC Voltage, EMF Test. There is a new reference for developing new composite materials by using metal lathe waste so as not to become waste. The material used is metal lathe waste arranged in the middle along the specimen and randomly with a volume fraction of 10% with variations in weight of one gram to five grams, using Polyester BQTN 157 as the matrix, making of mold. From the test results obtained the results of reinforced polyester composite metal lathe machine, has declination and the Inclination, angle meets the anti direct current (DC) voltage, does not have EMF.